2020
DOI: 10.1177/2192568220964051
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the OF Classification and Radiological Outcome of Osteoporotic Vertebral Fractures After Kyphoplasty

Abstract: Study Design: Retrospective cohort study. Objectives: The OF classification is a new classification for osteoporotic vertebral fractures. The aim of this study was to clarify the relationship between preoperative OF subgroups and the postoperative outcome after kyphoplasty in patients with such fractures. Methods: Patients who underwent kyphoplasty of a single osteoporotic vertebral fracture were included and divided into groups according to the OF subgroups. Pre- and postoperative plain radiographs were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The duration between the patients' admission and the treatment decision was 4 ± 4 days (range: 0-26, median 2 days) and did not differ depending on surgical or conservative therapy choice (P = .376). At the day of treatment decision the mean OF-score was 8.2 ± 1.7 (range [4][5][6][7][8][9][10][11][12] and differed between conservative (7.6 ± 1.8) and surgical treated patients (8.4 ± 1.7, P = .029). Thereby a total of 15 patients were treated conservatively despite an OF score of more than 6 and 7 patients were treated surgically despite an OF score of less than 6.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The duration between the patients' admission and the treatment decision was 4 ± 4 days (range: 0-26, median 2 days) and did not differ depending on surgical or conservative therapy choice (P = .376). At the day of treatment decision the mean OF-score was 8.2 ± 1.7 (range [4][5][6][7][8][9][10][11][12] and differed between conservative (7.6 ± 1.8) and surgical treated patients (8.4 ± 1.7, P = .029). Thereby a total of 15 patients were treated conservatively despite an OF score of more than 6 and 7 patients were treated surgically despite an OF score of less than 6.…”
Section: Resultsmentioning
confidence: 97%
“…Taking the recent literature into account stand-alone cement augmentation seems to be justified. Palmowski et al 4,12 reported of favorable clinical and radiological results with reduction potential and low reduction loss in the short run. Similarly, Gu et al 3 reported similar clinical results after both stand-alone kyphoplasty and hybrid stabilization.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Posterior stabilization was recommended in unstable fractures, such as OF type 3-5 fractures, depending on the clinical course. To date, several studies have evaluated the treatment of OVCFs using the OF score [2,[9][10][11][12], including the treatment of short-and long-segmental posterior stabilizations. Recently, OF classifications have gained an increased level of acceptance [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fragility fractures lead to physical disability, pain, impaired quality of life, increased mortality, and higher healthcare costs [5]. Therefore, treatment as well as preventive countermeasures for fractures should be instituted, as more elderly individuals are expected to experience fractures in the coming decade [6].…”
Section: Introductionmentioning
confidence: 99%